The level of customers awareness towards online service for motor takaful provided by Takaful Malaysia – Kuching Branch/ Zainuri Rakawi Sahari - Sahari, Zainuri Rakawi (2007)
The purpose of the study is to determine whether the participant aware and satisfied with the online service for motor Takaful provided by Takaful Malaysia. This is because some of the participant not aware with the existence of the service provided by Takaful Malaysia. This is because the participants still comfortable and willing to come to the counter for transactions. This study also to determined the level effectiveness on promotion that been done by Takaful Malaysia.